2010
DOI: 10.1007/s11010-010-0596-1
|View full text |Cite
|
Sign up to set email alerts
|

The α-isoform of class II phosphoinositide 3-kinase is necessary for the activation of ERK but not Akt/PKB

Abstract: Phosphoinositide 3-kinases (PI3Ks) are key enzymes that activate intracellular signaling molecules when a number of different growth factors bind to cell surface receptors. PI3Ks are divided into three classes (I, II, III), and enzymes of each class have different tissue specificities and physiological functions. The α-isoform (PI3K-C2α) of class II PI3Ks is considered ubiquitous and preferentially activated by insulin. Our previous study showed that suppression of PI3K-C2α leads to apoptotic cell death. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…We reported that phosphorylation of Akt at Ser 473 and of its downstream target GSK3β upon a short stimulation with insulin or PDGF was not affected by down-regulation of PI3K-C2α in L6 cells, consistent with the fact that the insulin-induced synthesis of PtdIns(3,4)P 2 and PtdIns(3,4,5)P 3 was not inhibited in these cells [20]. Recently, it has been demonstrated that ERK (extracellularsignal-regulated kinase), but not Akt Ser 473 , phosphorylation was inhibited in CHO-IR and HepG2 cells expressing antisense sequences targeting PI3K-C2α and stimulated with insulin for 10 min [69]. Furthermore, down-regulation of PI3K-C2α did not affect Akt (Ser 473 ) and GSK3β phosphorylation in HeLa cells in serum [57].…”
Section: Downstream Effectors a Downstream Effector Of Class II Pi3kssupporting
confidence: 77%
“…We reported that phosphorylation of Akt at Ser 473 and of its downstream target GSK3β upon a short stimulation with insulin or PDGF was not affected by down-regulation of PI3K-C2α in L6 cells, consistent with the fact that the insulin-induced synthesis of PtdIns(3,4)P 2 and PtdIns(3,4,5)P 3 was not inhibited in these cells [20]. Recently, it has been demonstrated that ERK (extracellularsignal-regulated kinase), but not Akt Ser 473 , phosphorylation was inhibited in CHO-IR and HepG2 cells expressing antisense sequences targeting PI3K-C2α and stimulated with insulin for 10 min [69]. Furthermore, down-regulation of PI3K-C2α did not affect Akt (Ser 473 ) and GSK3β phosphorylation in HeLa cells in serum [57].…”
Section: Downstream Effectors a Downstream Effector Of Class II Pi3kssupporting
confidence: 77%
“…For PI3KC2β it was shown that this enzyme can promote LPA-induced cell migration of ovarian and cervical cancer cells (Maffucci et al 2005; for a review on class II PI3K in cancer see (Traer et al 2006)). Other results point to a role of class II PI3Ks in insulin signaling (Cui et al 2011;Dominguez et al 2011), which is supported by the finding that class II regulates exocytosis of insulin granules in pancreatic beta cells (Dominguez et al 2011). Interestingly, a polymorphism in the PIK3C2G gene (encoding PI3KC2γ could be associated with type 2 diabetes in a Japanese population (Daimon et al 2008)), and the nematode C. elegans accumulates fat when its only class II PI3K gene (F39B1.1) product is down-regulated.…”
Section: Class II Pi3ksmentioning
confidence: 86%
“…The available data connects class II PI3Ks to multiple signaling events like the activation of MAPK (but not PKB/Akt (Cui et al 2011)), activation of Ca 2+ -triggered potassium channels (KCa3.1; Srivastava et al 2009), the regulation of Rho (Wang et al 2006), clathrin coated vesicular movement on microtubules (Zhao et al 2007), exocytosis (Meunier et al 2005) and endocytotic events mentioned above. For class II PI3Ks it is presently not possible to delineate connected signaling pathways, and to define a predictive network linked to general signaling outputs.…”
Section: Class II Pi3ksmentioning
confidence: 99%